2000
DOI: 10.1161/01.cir.101.8.850
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Patients at Increased Risk of First Unheralded Acute Myocardial Infarction by Electron-Beam Computed Tomography

Abstract: Background-There is a clear relationship between absolute calcium scores (CS) and severity of coronary artery disease.However, hard coronary events have been shown to occur across all ranges of CS. Methods and Results-We conducted 2 analyses: in group A, 172 patients underwent electron-beam CT (EBCT) imaging within 60 days of suffering an unheralded myocardial infarction. In group B, 632 patients screened by EBCT were followed up for a mean of 32Ϯ7 months for the development of acute myocardial infarction or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
417
3
25

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 789 publications
(465 citation statements)
references
References 47 publications
18
417
3
25
Order By: Relevance
“…As in other populations, coronary artery calcium scores increased with age 13,16,17 ; however, the non-Gaussian distribution and the small number of individuals in the age groups > 60 years in our sample jeopardized the better comparison of coronary artery calcification between that age group and those immediately below and above it. Although the medians are greater, no statistical difference was observed in these values.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…As in other populations, coronary artery calcium scores increased with age 13,16,17 ; however, the non-Gaussian distribution and the small number of individuals in the age groups > 60 years in our sample jeopardized the better comparison of coronary artery calcification between that age group and those immediately below and above it. Although the medians are greater, no statistical difference was observed in these values.…”
Section: Discussioncontrasting
confidence: 58%
“…Therefore, it is necessary that other tests be used for a better stratification of the risks for coronary events. Data from the literature have shown that the presence of coronary artery calcification is associated with a greater risk for coronary events [11][12][13][14] , and its absence is associated with an almost-zero risk for coronary events in studies of 3-to-5 year follow-up 25 . Coronary artery calcium scores have their major usefulness in stratifying the risk for clinical events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the SYNTAX score did not predict long-term clinical outcomes, the CSS was useful in predicting the 1-year major adverse cardiac and cerebrovascular events, reflecting the potentially significant impact of the patient's clinical and demographic factors such as their ages on their clinical outcomes [34] . Previous studies have also shown that age is significantly associated with increased coronary artery calcium score [35,36] . Calcification of the coronary system is associated with coronary artery disease (CAD) and coronary artery calcium content is highly associated with increased cardiovascular events [36] .…”
Section: Coronary Lesions Complexitymentioning
confidence: 86%
“…Previous studies have also shown that age is significantly associated with increased coronary artery calcium score [35,36] . Calcification of the coronary system is associated with coronary artery disease (CAD) and coronary artery calcium content is highly associated with increased cardiovascular events [36] .…”
Section: Coronary Lesions Complexitymentioning
confidence: 86%